Improving photoresponsivity in GaAs film grown on Al-induced-crystallized Ge on an insulator - T. Nishida; T. Suemasu; K. Toko (AIP Advances, 2020)
The highest recorded photoresponsivity in polycrystalline GaAs films on glass has been updated by precisely controlling the growth temperature of GaAs on a Ge seed layer formed by Al-induced layer exchange. X-ray diffraction and electron backscatter diffraction analyses showed that large-grained (>100 µm) GaAs (111) films epitaxially grew from the Ge layer above 510 °C. According to energy dispersive x-ray and Raman spectra, 550 °C was the optimum growth temperature that allowed for the growth of high-quality GaAs film with a stoichiometric composition. Reflecting the high crystallinity, the internal quantum efficiency reached 90% under a bias voltage of 0.3 V. Low-temperature GaAs films grown on inexpensive substrates will make the development of advanced solar cells that achieve both high efficiency and low cost possible.